2005
DOI: 10.1038/sj.bjp.0706421
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester modulates Helicobacter pylori‐induced nuclear factor‐kappa B and activator protein‐1 expression in gastric epithelial cells

Abstract: 1 Caffeic acid phenethyl ester (CAPE), an active component of propolis from honeybee hives (honeybee resin), has anti-inflammatory, anti-carcinogenic and anti-bacterial properties. This study was designed to investigate the anti-inflammatory effects of CAPE on Helicobacter pylori-induced NF-kB and AP-1 in the gastric epithelial cell line AGS. 2 Electrophoretic mobility shift assay was used to measure NF-kB-and AP-1-DNA binding activity. Western blotting was used to detect IkB-a and COX-2 expression in AGS cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…1 T cells and the gastric epithelium [36,37], we could show that phosphorylation of NF-kB and IkBa, degradation of IkBa and RelA nuclear translocation were unchanged in Mode-K cells after CAPE treatment, suggesting that effects are cell/tissue type-specific. However, our results are in agreement with two previous reports which demonstrated that CAPE has no effect on IkBa degradation in osteoclasts [38] and U937 cells [7].…”
Section: Discussionmentioning
confidence: 84%
“…1 T cells and the gastric epithelium [36,37], we could show that phosphorylation of NF-kB and IkBa, degradation of IkBa and RelA nuclear translocation were unchanged in Mode-K cells after CAPE treatment, suggesting that effects are cell/tissue type-specific. However, our results are in agreement with two previous reports which demonstrated that CAPE has no effect on IkBa degradation in osteoclasts [38] and U937 cells [7].…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, NF-κB activation is thought to link with oxidative stress, cytotoxic cytokines and liver cell necrosis (Liu et al, 1995). CAPE is a well-documented inhibitor of NF-κB (Abdel-Latif et al, 2005;Natarajan et al, 1996), by intervening in IKK-IκBα-p65 pathway or activating nuclear factor erythroid 2 related factor 2 (Nrf2) (Ang et al, 2009;Onori et al, 2009;Toyoda et al, 2009;Lee et al, 2010). Nrf2, an important cytoprotective transcription factor, binds to antioxidant responsive element and is a chief regulator of a battery of cytoprotective genes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, interest in CAPE has increased not only as a potential active pharmacologic agent but also mainly as prospective raw material for pharmaceutical industry as either a starting or intermediate material for the synthesis of closely related compounds. Numerous pharmacological activities have been reported for CAPE including anticancer/tumor [2,3], antiviral [4,5], anti-inflammatory [6,7], and antioxidant [8][9][10]. Our previous studies have identified a newly synthesized CAPE derivative, FCAPE (Fig.…”
Section: Introductionmentioning
confidence: 98%